2012
DOI: 10.1210/en.2011-1792
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod Regulates Vitamin A and Wnt/β-Catenin Signaling in F344 Rats

Abstract: In seasonal mammals, growth, energy balance, and reproductive status are regulated by the neuroendocrine effects of photoperiod. Thyroid hormone (TH) is a key player in this response in a number of species. A neuroendocrine role for the nutritional factor vitamin A has not been considered, although its metabolic product retinoic acid (RA) regulates transcription via the same nuclear receptor family as TH. We hypothesized that vitamin A/RA plays a role in the neuroendocrine hypothalamus alongside TH signaling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 52 publications
5
82
0
Order By: Relevance
“…Further evidence for the involvement of vitamin A and RA in growth and energy balance comes from the study of photoperiodic animals such as hamsters which display increased growth and feeding under long day (summer‐like) conditions compared to short (winter‐like) daylength. Many components of the RA signalling pathway are upregulated in the hypothalamus of long day‐acclimatized rodents including the retinoic X receptor (RXR) which can heterodimerize with either the TH receptor or the RA related receptor (Helfer et al, 2012; Ross et al, 2005; Ross et al, 2004; Shearer et al, 2010; Shearer et al, 2012b). Finally, the importance of Raldh1 in energy balance is highlighted in the finding that Raldh1 −/− mice are highly resistant to diet‐induced obesity (Ziouzenkova et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further evidence for the involvement of vitamin A and RA in growth and energy balance comes from the study of photoperiodic animals such as hamsters which display increased growth and feeding under long day (summer‐like) conditions compared to short (winter‐like) daylength. Many components of the RA signalling pathway are upregulated in the hypothalamus of long day‐acclimatized rodents including the retinoic X receptor (RXR) which can heterodimerize with either the TH receptor or the RA related receptor (Helfer et al, 2012; Ross et al, 2005; Ross et al, 2004; Shearer et al, 2010; Shearer et al, 2012b). Finally, the importance of Raldh1 in energy balance is highlighted in the finding that Raldh1 −/− mice are highly resistant to diet‐induced obesity (Ziouzenkova et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This phenotype was ascribed to an excess of retinaldehyde in adipose tissue due to a lack of Raldh1. However, more recent studies have identified Raldh1 as the only RA‐synthesizing enzyme in the mouse hypothalamus (Helfer et al, 2012; Shearer et al, 2010) and therefore the downregulation of hypothalamic RA signalling in Raldh1 −/− mice may also play a role in prevention of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Another study provides strong evidence for a novel endocrine axis, involving the nutrient vitamin A regulated by photoperiod and melatonin and suggest a role for several new players in the photoperiodic neuroendocrine response. Melatonin is known to mediate the physiological effects of short-day photoperiod in mammals 55,56 .…”
Section: Resultsmentioning
confidence: 99%
“…In the photoresponsive rat strain Fischer 344, the retinoic acid (RA) signaling pathway is also activated in LD conditions (Helfer et al 2012, Tavolaro et al 2015.…”
Section: Regulatory Mechanism For Mammalian Seasonal Reproductionmentioning
confidence: 99%